Assessment of microbiological activities of empurau fish (Tor Tambraides) of local fish farm - Famila Farvin, Binti Ghulam Dasthagir (Universiti Malaysia Sarawak (UNIMAS), 2012)
Enterobacteriaceae is a member of gram-negative bacilli and contain more than 30 genera. They act as the main indicator for the bacteriological water quality. Study was conducted to determine the occurrence of Enterobacteriaceae family in Empurau (Tor Tambraides) pond at Indigenous Fish Research & Production Centre (IFRPC) in Tarat, Sarawak in which this it could reflect the level of microbe found in the pond. Studies also been conducted for detection on any possible pathogenic bacteria that might cause infectious disease in fish pond. Besides that, studies were conducted for determining the relationship between physicochemical parameter and microbiological parameter with the development of the fish in the pond. Water sample from the pond were collected and analyzed for the presence of Enterobacteriaceae. Sample plated on Nutrient Agar and colonies formed were tested on gram staining. Colonies with Gram-negative were further analyzed with (GTG)5 PCR. The phylogenetic tree was constructed based on the DNA fingerprinting to illustrate the relationship among the bacteria isolates. 11 randomly picked samples were tested with API 20E kit for identification of the bacteria.